The Impact of Plagiarism on Doctoral Education in Indonesia - Maulana, Arman; Rosmayati, Siti; Nuraeni, Yayang Ayu (Yayasan Azka Hafidz Maulana, 2023)
Plagiarism is a serious problem in doctoral education in Indonesia that has widespread detrimental impacts. This paper presents an analysis of the impact of plagiarism on doctoral education in Indonesia. This research includes literature studies and related data that describe the prevalence of plagiarism, causes, and consequences of plagiarism in the context of doctoral education. Plagiarism hinders the doctoral education process by damaging academic integrity, reducing trust in research and researchers, and harming the reputation of educational institutions. This negative impact can affect the academic career progress of doctoral students and hinder innovation and knowledge development. This article also highlights the importance of preventive measures and effective law enforcement to overcome the problem of plagiarism in doctoral education in Indonesia. Collaborative efforts between educational institutions, government and society need to be increased to ensure academic integrity is maintained and doctoral education makes a valuable contribution to the development of science and technology in Indonesia